Postilla. Costituzione ed emergenza: verso la fine del tunnel, con qualche speranza e (ancora) con qualche dubbio (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
Two months after the beginning of the toughest phase of the Coronavirus pandemic emergency, our country hardly begins to rebuild – as far as possible – that normalcy ripped by the sudden rapid evolution of the contagion. In this time, we have experienced the most imposing limitation of fundamental rights and freedoms since the war, a concentration of emergency measures like never before. This contribution, taking up the reflections carried out, in the first instance, in the essay “Constitution and emergency. The Coronavirus experience” carries out some additional reflections on the emergency management regulatory procedures, and on the impact it has had on the most important and fragile resources of a democratic society: the rights and freedoms constitutionally protected.
Keywords: CoViD-19; pandemic emergency; emergency measures; Constitutional rights and freedoms; healthcare